2019
DOI: 10.1186/s12931-019-1148-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic factors underlying persistent pulmonary hypertension of newborns in a cohort of Chinese neonates

Abstract: Background Persistent pulmonary hypertension of the newborn (PPHN) is a severe clinical problem among neonatal intensive care unit (NICU) patients. The genetic pathogenesis of PPHN is unclear. Only a few genetic polymorphisms have been identified in infants with PPHN. Our study aimed to investigate the potential genetic etiology of PPHN. Methods This study recruited PPHN patients admitted to the NICU of the Children’s Hospital of Fudan University from Jan 2016 to Dec 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…In vitro studies using cells expressing these mutant Notch3 receptors, revealed increased cell viability and proliferation suggesting that these mutations have a gain-of-function action on Notch3 signalling [80]. More recently, another group also identified a synonymous single nucleotide polymorphism (SNP) in NOTCH3 (A2146A) as significantly associated with persistant PH of the newborn in a Chinese cohort, with detection in three patients [81].…”
Section: Notch3 Signalling In Pathological Vascular Remodelling-implimentioning
confidence: 99%
“…In vitro studies using cells expressing these mutant Notch3 receptors, revealed increased cell viability and proliferation suggesting that these mutations have a gain-of-function action on Notch3 signalling [80]. More recently, another group also identified a synonymous single nucleotide polymorphism (SNP) in NOTCH3 (A2146A) as significantly associated with persistant PH of the newborn in a Chinese cohort, with detection in three patients [81].…”
Section: Notch3 Signalling In Pathological Vascular Remodelling-implimentioning
confidence: 99%
“…CPS1 and SMAD9 were identified as risk genes for persistent PH of the newborn. 6 Currently, no BMPR-2 mutation associated to DS had been reported in this setting.…”
Section: Discussionmentioning
confidence: 95%
“…Nine patients were identified as harboring genetic variants, including three with pathogenic/likely pathogenic variants in TBX4 and BMPR-2 and six with variants of unknown significance in BMPR-2 , SMAD9 , TGFB1 , KCNA5 and TRPC6 . 6 Three single nucleotide polymorphisms (SNPs) in CPS1 and one SNP in NOTCH3 were significantly associated with persistent PH of the newborn. CPS1 and SMAD9 were identified as risk genes for persistent PH of the newborn.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of idiopathic PAH (IPAH) patients identified a number of mutations in the promoter and coding regions of KCNA5 believed to affect its transcription, trafficking, and interaction with its β subunits [17,18]. A new variant has also been found in Pulmonary Hypertension of the Newborn (PPHN) [19] Transient Receptor Potential Canonical (TRPC) channels are a subfamily of non-selective cation channels, which represent a major alternative route of Ca 2+ entry outside voltage-gated Ca 2+ channels, by functioning as both store-operated (SOC) and receptor-operated (ROC) channels [20]. Pharmacological blockade and knockout experiments found a strong correlation between TRPC6 expression, capacitative Ca 2+ entry, resting cytoplasmic [Ca 2+ ], vascular tone and proliferation of rat PASMCs [21].…”
Section: Overview Of Channelopathies In Pahmentioning
confidence: 99%